Pengembangan Media Pembelajaran Berbantuan Movie Maker pada Materi Drama bagi Siswa Kelas XI Sekolah Menengah Kejuruan Madani Marindal I - Suryani, Intan; Ali, Ali; Amaluddin, Amaluddin (Medan Resource Center, 2025)
This study investigates the development, feasibility, and effectiveness of instructional media utilizing Movie Maker software to support the teaching of drama material for eleventh-grade students at SMK Madani Marindal I. Employing the ADDIE development model—comprising Analysis, Design, Development, Implementation, and Evaluation—the research involved a total population of 46 students, with a purposive sample of 22 participants. The findings indicate that the developed media was deemed suitable for instructional use. Evaluations by media experts revealed a